2022
DOI: 10.1101/2022.05.06.489035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synovial fibroblasts assume distinct functional identities and secrete R-spondin 2 to drive osteoarthritis

Abstract: ObjectivesSynovium is acutely affected following joint trauma and contributes to post-traumatic osteoarthritis (PTOA) progression. Little is known about discrete cell types and molecular mechanisms in PTOA synovium. We aimed to describe synovial cell populations and their dynamics in PTOA, with a focus on fibroblasts. We also sought to define mechanisms of synovial Wnt/β-catenin signaling, given its emerging importance in arthritis.MethodsWe subjected mice to non-invasive anterior cruciate ligament rupture as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In recent years, the rapid progress in single‐cell RNA sequencing, spatial transcriptomics, fate‐mapping, and multiplexed immunohistochemical technologies has revealed the unexpected diversity in macrophages. Indeed, several studies have demonstrated the synovial macrophage diversity during the pathogenesis in the OA, 224–226 and in‐depth research focusing on the distinct functions, origins, and disease kinetics of macrophage subtypes would be indispensable for targeting these versatile cells.…”
Section: Future Directionsmentioning
confidence: 99%
“…In recent years, the rapid progress in single‐cell RNA sequencing, spatial transcriptomics, fate‐mapping, and multiplexed immunohistochemical technologies has revealed the unexpected diversity in macrophages. Indeed, several studies have demonstrated the synovial macrophage diversity during the pathogenesis in the OA, 224–226 and in‐depth research focusing on the distinct functions, origins, and disease kinetics of macrophage subtypes would be indispensable for targeting these versatile cells.…”
Section: Future Directionsmentioning
confidence: 99%
“…Physiological data were correlated with expression data of individual genes with gene significance (GS). The visualization of the co-expression network and the recognition of the hub gene in each module were achieved through Cytosscape software v3.91 (Knights et al, 2022).…”
Section: Wgcnamentioning
confidence: 99%